The Memory of Wood: Italian Past, Canadian Experiences - Palusci, Oriana (Italian Canadiana)

(untitled) (Iter Press, 2023)
In this essay, I try to connect Italian migration and life in Canada through the memory of wood, taking as case studies wooden relics made in Italy and relocated to a country known for its immense forests, as well as wooden artifacts made in Canada by the Italian newcomers. After briefly introducing some general observations on the Italian-Canadian community, employing a Cultural Studies approach, I deal with different experiences undergone by Italians, both as new citizens and, as in the case of Giuseppe Penone, as artists working in Canada. Ranging from unfair treatment during the Second World War to the creation of the Galleria Italia in the AGO in Toronto, wood is a relevant keynote in the construction of a hybridized Italian-Canadian culture. Specific wooden objects, such as trunks and Catholic crosses, are taken into account with reference to a thriving Italian-Canadian literary milieu. In conclusion, I demonstrate that Italian popular culture has also left a trace in the Canadian experience.